Seeded batch cooling crystallization with temperature cycling for the control of size uniformity and polymorphic purity of sulfathiazole crystals - Abu Bakar, Mohd Rushdi; Nagy, Zoltan K.; Rielly, Chris D. (American Chemical Society, 2009)
An experimental study has been conducted to evaluate the capability of a seeded batch cooling crystallization with a temperature cycling method to produce a narrow crystal size distribution and grow a desired polymorphic form of sulfathiazole crystals. The study used focused beam reflectance measurement (FBRM), and attenuated total reflectance ultraviolet/visible (ATR-UV/vis)spectroscopy for the in situ monitoring and control of the process. Based on the FBRM readings, the process was driven using a feedback control approach that employs alternating cycles of heating and cooling phases so that the number of counts, corresponding to the number of seed particles, is maintained, whilst the square-weighted chord length distribution, indicating the dynamic progress of the growth of the seeds in the system, is increased. Results of the experiments show that the temperature cycling method promoted Ostwald ripening, which helped in accelerating the growth and enhancing the size uniformity of the product. The method also has a good prospect to be implemented for the control of polymorphic purity. Seeds of Form I and Form II could be grown from n-propanol and water, respectively. Form I seeds in water were first transformed into Form II and/or swamped by nuclei of Form II, before the growth of the newly formed crystals took place. Seeds of Form II and Form III in n-propanol, however, were not able to grow at all. This study confirmed that the nucleation and growth of sulfathiazole crystals are solvent-mediated, and the insight into these phenomena was captured very well by the in situ monitoring tools.